MAGMA-CRUST INTERACTIONS AND MAGMA PLUMBING IN A POSTCOLLISIONAL SETTING: GEOCHEMICAL EVIDENCE FROM THE ERZURUM-KARS VOLCANIC PLATEAU, EASTERN TURKEY - Keskin M.; Pearce J.A.; Kempton P.D.; Greenwood P. (My University, 2006)
In Northeastern Anatolia, the Erzurum-Kars plateau comprises the northernmost part of a volcanic province related to the collision between the Eurasian and Arabian continents. It contains an almost complete record of the volcanism from 11 Ma to 1.5 Ma. Volcanic units on the plateau are calc-alkaline in character and contain a distinct subduction signature. There was a systematic temporal variation in volcanic activity all over the plateau that can be seen in terms of three stages: it initiated with bimodal volcanic products between 11 and 6 Ma (the early stage), turned abruptly into a unimodal intermediate volcanism dominated by andesitic lavas between 6 and 5 Ma (the middle stage), and finally reverted to bimodal activity between 5 and 1.5 Ma (the late stage). These three stages were diachronous as the volcanic succession got progressively younger from the west to the east. The temporal variations were strongly dependent upon the depth of the magma chambers from which the volcanic products were derived. Lavas of the early and late stages were derived from relatively shallow chambers (<10-13 km) that fractionated anhydrous phases and assimilated a minor amount of crustal material or none. in contrast, those the middle stage were sourced by large, deeper (>13 km), compositionally zoned chambers where amphibole was a fractionating phase and assimilation and fractional crystallization was an important process. The isotopic compositions of the volcanic units do not exhibit a systematic temporal variation on the Erzurum-Kars plateau; instead they exhibit spatial changes. Lavas from the western part of the plateau are much more unradiogenic in terms of their Pb isotopic ratios than those from the eastern part. These variations are possibly related to the composition and the amount of crustal material assimilated by the magmas, and hence indicate the existence of two different and isotopically distinct crustal domains beneath the plateau: (1) the Rhodope-Pontide fragment in the west and (2) the Northwest Iranian fragment in the east. © 2006 Geological Society of America.
Keywords: ASSIMILATION AND FRACTIONAL CRYSTALLIZATION; CONTINENTAL COLLISION; CRUSTAL DOMAINS; EASTERN ANATOLIA; MAGMA PLUMBING; ASSIMILATION; O, SR, ND, AND PB ISOTOPES; VOLCANISM